Appointment as Reviewer, 2011 - Lau, S. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Appreciation in reviewing the article "Photochemical and Photocatalytic Degradation of Diclofenac andAmoxillin using natural and simulated Sunlight"